The White Worsted Thread: Third Space Encounters in English L2 Writing – A Theoretical Framework for Understanding Writing for Publication in English - Keranen, Nancy; Barbosa-Trujillo, Rocio; Encinas, Maria Teresa Fatima (Journal of Academic Writing, 2016)
This paper aims to propose a theoretical framework for investigating L2 speaking scholars who successfully write in English for publication. The theories brought together – which are associated with third space, hybridity, funds of knowledge, intertextuality, heteroglossia and multivoicedness – form a nest of interrelated theories which proved useful for examining writing for publication by non-native English speaking (NNES) academics in our own work (Barbosa-Trujillo 2015, Barbosa-Trujillo and Keranen 2015). The paper first orients the topic within the field of NNES scientific research writing then discusses the theoretical framework presented, first by pulling the strands apart to briefly describe each, then by showing how each strand works within the framework as a foundation for research.